Comparisons of the chondroitin sulphate levels in orthodontically moved canines and the clinical outcomes between two different force magnitudes - Kanlaya Insee (2018)
The aims of this study were to compare the chondroitin sulphate (CS) levels in gingival crevicular fluid (GCF) of moved canines using either 70 or 120g of orthodontic force, and to compare the rate of tooth movement and the amount of pain between these two force magnitudes. Sixteen patients (6 male s and 10 females; aged 16.91±2.99 years), with class I malocclusion, who required orthodontic treatment with first premolar extractions, were recruited. The force magnitudes used to move the maxillary canines distally were controlled at 70 and 120g on the right and the left sides, respectively. GCF samples were collected with Periopaper ® strips before and during orthodontic tooth movement. Competitive ELISA with monoclonal antibody was used to measure the CS levels. The distance of tooth movement and the amount of pain assessed by visual analog scale (VAS) scores were evaluated. The medians of CS levels during the loaded period were significantly greater than those during the unloaded period (P < 0.05). The differences between the medians of CS levels of 70g and 120g retraction force during each 1 week period were not significant. There was no significant difference in the rates of canine movement between these two force magnitudes. However, using 120g, the medians of VAS scores were significantly greater than those with 70g (P < 0.05). Collectively, 70g retraction force appears to be sufficient and more suitable than 120g force as it causes no difference in biochemically-assessed bone remodelling activity, the same rate of tooth movement, reduced pain and better comfort. © 2013 © The Author 2013. Published by Oxford University Press on behalf of the European Orthodontic Society. All rights reserved.